THE INFLUENCE OF EMPLOYEE PERCEPTION AND ORGANIZATIONAL CULTURE TO ORGANIZATIONAL CHANGE AT PT HONDA MARTADINATA 2 MANADO - Lembong, Verent V. R.; Tumbuan, Willem J. F. A.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The purpose of this study is to evaluate the influence of employee perception and organizational culture on organizational change at PT. Honda Martadinata 2, Manado. Employee perception is one of the factors that have big impact on the process of successfully implemented change, it supports by giving each of employees an individual's view to get variance strategy from the different employees on facing organizational change. Therewith, organizational culture guides the process of change, by ensuring the leader and employees have a positive relation to making the process be effective and efficient. Organizational culture becomes the foundation to support organizational change. The data of this research was collected through an online survey questionnaire using slovin sampling technique of 63 employees of PT. Honda Martadinata 2, Manado. The findings may be useful for the organization to understand better about how the organizational change to be successful and reduce the negative reaction towards the change process on the organization.Keywords: Employee Perception, Organizational Culture, Organizational Change